Пошук образів за силуетами яскравості зображень - Мельник, Р.А.; Каличак, Ю.І. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
An approach to find different types of a pattern brightness silhouettes which then are being replaced by polynomial coefficients of approximation functions is considered. Coefficients and silhouette diagrams of visual patterns were tested as image features for searching them in the databases.